Prevalence and Risk Factors of Bruxism in a Selected Population of Iranian Children - Fatemeh Jahanimoghadam; Mahsa Tohidimoghadam; Hamidreza Poureslami; Maryam Sharifi (Association of Support to Oral Health Research (APESB), 2023)
Objective: To investigate the prevalence of bruxism in Iranian children aged 6 to 12 years. Material and Methods: This cross-sectional study was conducted on 600 schoolchildren aged 6-12 years. The questionnaire consisted of two sections: the first section included demographic information, while the second evaluated the occurrence of bruxism. Kruskal-Wallis, Chi-Square, Fisher and Multinomial logistic regression were used. A level of p<0.05 was considered statistically significant. Results: 698 questionnaires were distributed, of which 600 participants were returned. According to Multinomial logistic regression, awake bruxism was associated significantly with the following variables: age, sequence of birth, recurrent headache, gastrointestinal disease, nasal obstruction, neurological disorder, easy child crying, sleep disorders, talking in a dream and snoring and jaw disorder. Sleep bruxism was associated significantly with age, premature birth, allergy, gastrointestinal disease, drooling, mouth breathing, nasal obstruction, oral habit, nail biting, sleep disorder, jaw disorders, and family history. Conclusion: Pre-birth and post-birth factors play an important role in the prevalence of bruxism in society. It is possible to prevent complications of bruxism by informing parents and making a timely diagnosis. Parents should be aware of this occurrence to reduce possible related factors to teeth and the masticatory system.